AB0940 Comparison of US7 and US10 Risk Scores in Early Inflammatory Arthritis (EIA). (15th July 2016) - Rawlings, C.; Davies, R.; Choy, E.
Abstract : Background: Ultrasound (US) can anticipate joint damage better than DAS28 [1], correlates well with MRI [2] and can be of value determining persistence of EIA [3]. US scoring systems aim to standardise risk assessment. US10 risk score showed clinical utility in predicting benefit from early biologic therapy [4]. The US7 score reflects arthritis therapeutic response [5]. No study has directly compared these US scores. Objectives: Compare measurement performance of US7 and US10 scores in assessing EIA. Methods: 32 EIA patients were examined by 2 trained musculoskeletal US Rheumatologists. 52 DAS28 scores and US7/US10 risk assessments were completed. Inter-observer variability was assessed by intraclass correlation coefficient (ICC). Criterion validity assessed by Pearson correlation with DAS28. Results: Mean age 57 (SD=14), 24/32 (75%) female, 28/32 (87.5%) anti-CCP positive, 27/32 (84%) RF positive. Inter-observer variability (ICC) for US10 and US7 were 0.57 (P<0.0001) and 0.73 (P<0.0001) respectively. DAS28 correlation with US7 (r=0.335, P=0.018) and US10 (r=0.095, P=0.514). US7 and US10 correlated with swollen joint count (r=0.499, P=0.000) and (r=0.368, P=0.006). The addition of wrist US improved DAS28 correlation with US10 (r=0.255, p=0.077). Conclusions: Inter-observer variability is moderate to good with US7 and US10. US7 and US10 correlates with SJC. US7 score in comparison with US10, correlates with the DAS28. Addition of wrist US score to US10 improved correlation with DAS28. This could be a more time effective method to stratify patients if feet assessment is not feasible. References: Radunovic G, Prodanovic S, Vukovic V, Milic V, Simic Pasalic K, Jablanovic D, Seric S, Milutinovic S, Gavrilov N. Rheumatology (Oxford). 2012 Jan;51(1):120–8. doi:10.1093/rheumatology/ker255. Epub 2011 Nov 8. Construct validity and reliability of ultrasound disease activity score in assessing joint inflammation in RA: comparison with DAS-28. Szkudlarek, M., Court-Payen, M., Strandberg, C., Klarlund, M., Klausen, T. and Østergaard, M. (2001), Power doppler ultrasonography for assessment of synovitis in the metacarpophalangeal joints of patients with rheumatoid arthritis: A comparison with dynamic magnetic resonance imaging. Arthritis & Rheumatism, 44: 2018–2023. Freeston JE, Wakefield RJ, Conaghan PG, Hensor EM, Stewart SP, Emery P. A diagnostic algorithm for persistence of very early inflammatory arthritis: the utility of power Doppler ultrasound when added to conventional assessment tools. Ann Rheum Dis. 2010 Feb;69(2):417–9. D. Sreerangaiah, M. Grayer, B. A. Fisher, M. Ho, S. Abraham, P. C. Taylor. Quantitative power Doppler ultrasound measures of peripheral joint synovitis in poor prognosis early rheumatoid arthritis predict radiographic progression. Rheumatology 2016;55:89_93. Arthritis & Rheumatism (Arthritis Care & Research) Vol. 61, No. 9, September 15, 2009, pp 1194–1201 DOI 10.1002/art.24646 Evaluation of a Novel 7-Joint Ultrasound Score in Daily Rheumatologic Practice: A Pilot Project M. Backhous, S. Ohrndorf, H. Kellner, J. Strunk, T. M. Backhaus, W. Hartung, H. Sattler, K. Albrecht, J. Kaufmann, K. Becker, H. Sörensen, L. Meier, G. R. Burmester, and W. A. Schmidt. Disclosure of Interest: None declared